Building Islamic Legal Awareness in Young Santri: The Dynamics of Taklif Understanding and Application in Islamic Boarding School - Taufikin, Taufikin; Hadi, Solikhul; Kusumawati, Ita Rahmania (FENOMENA, 2025)
Applying taklif to children's students is part of learning religious traditions (Islamic law), which aims to shape Islamic character from an early age. In implementing taklif, there are challenges, especially related to children's cognitive limitations in understanding abstract sharia laws such as mubah and makruh. In addition, traditional implementation methods are often ineffective in conveying the concept of taklif to children. This study aims to analyze the application of taklif to child santri by learning about religious traditions, identifying factors that influence their understanding, and evaluating the effectiveness of taklif learning methods applied in pesantren. Through a case study approach, this research collects data through observation, in-depth interviews, and documentation to thoroughly understand the process of learning taklif as Sharia law in pesantren. The results showed that children more easily understand the obligatory and sunnah laws because they are concrete and often practiced in everyday life. In contrast, the laws of mubah and makruh are challenging to understand because they are more abstract. The pesantren environment, parental involvement, and learning methods such as short lectures, hands-on practice, and educational games are important in improving Santri's understanding. This research provides recommendations for pesantren to develop more adaptive and innovative learning methods for learning Taklif in children and additional insights for parents about the importance of traditionalizing an understanding of Islamic law early on in children.